Running in people with cerebral palsy: A systematic review - Chappell, A.; Gibson, N.; Morris, S.; Williams, G.; Allison, Garry (2018)
Background: Running is a fundamental motor skill which is important for participation in recreational activities throughout the lifespan. Aim: To identify, appraise, and synthesize the evidence related to running in people with cerebral palsy (CP). Method: A search of electronic databases was conducted in April 2016. Articles were reviewed by two assessors and had to meet the following criteria: 1) population included people with CP; and 2) included information about running. Articles were assessed for quality using the Checklist for Measuring Study Quality by Downs and Black. Results: Of 2607 articles initially identified, 56 underwent full-text review and 17 were included. Quantitative analysis was not possible. The quality of descriptive studies was fair-good, while intervention studies scored poor-good. Four of the 12 descriptive studies reported kinematic and kinetic data. Five intervention studies included running as an outcome measure, although running was not the focus of intervention. A few studies showed that sprint speed, agility, and running efficiency are impaired in people with CP, but mechanisms underlying these impairments have yet to be reported. Interpretation: Research on running in people with CP is limited, methodology and findings are inconsistent and studies are generally fair quality. Further investigation is warranted.